To Never See Death: Yeats, Reincarnation, and Resolving the Antinomies of the Body-Soul Dilemma - C. Nicholas Serra (Religions, 2017)
This essay addresses the ideas and schemas of reincarnation as used in the poetry and prose of William Butler Yeats, with particular focus on the two editions of A Vision. It contrasts the metaphysical system as given in A Vision (1937) with a number of inconsistencies found in Yeats’s poetic corpus, with an emphasis on how one might interpolate an escape from the cycle of lives, in at least one possibility while still maintaining corporality. The justification for this last comes from an analysis of complex cabalistic metaphors and teachings that Yeats learned as a member of MacGregor Mathers’ Hermetic Order of the Golden Dawn.